Understanding organizational memory from the integrated management systems - Perez, Gilberto (2013)
With this research, in the form of a theoretical essay addressing the theme of Organizational Memory and Integrated Management Systems (ERP), we tried to present some evidence of how this type of system can contribute to the consolidation of certain features of Organizational Memory. From a theoretical review of the concepts of Human Memory, extending to the Organizational Memory and Information Systems, with emphasis on Integrated Management Systems (ERP) we tried to draw a parallel between the functions and structures of Organizational Memory and features and characteristics of ERPs. The choice of the ERP system for this study was made due to the complexity and broad scope of this system. It was verified that the ERPs adequately support many functions of the Organizational Memory, highlighting the implementation of logical processes, practices and rules in business. It is hoped that the dialogue presented here can contribute to the advancement of the understanding of organizational memory, since the similarity of Human Memory is a fertile field and there is still much to be researched.